2004
DOI: 10.1128/jcm.42.8.3626-3634.2004
|View full text |Cite
|
Sign up to set email alerts
|

MICs of Selected Antibiotics forBacillus anthracis,Bacillus cereus,Bacillus thuringiensis, andBacillus mycoidesfrom a Range of Clinical and Environmental Sources as Determined by the Etest

Abstract: This paper presents Etest determinations of MICs of selected antimicrobial agents for 76 isolates of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
87
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 33 publications
(28 reference statements)
10
87
1
4
Order By: Relevance
“…All isolates were sensitive to twelve different Gram (+)ve specifi c and broad spectrum antibiotics (Table 1). Broadly, the isolates were resistant to the penicillin group but strictly, the BT1 and 2 were resistant to penicillin, ampicillin and amoxicillin; BT4 was resistant to penicillin and ampicillin and BT5 is resistant to ampicillin and amoxicillin (Table 1) which was in agreement with other Bt 4,9 . The biochemical and physiological characters revealed that the BT3, 7, 9, 11 and 12 were similar i.e.…”
Section: Introductionsupporting
confidence: 77%
“…All isolates were sensitive to twelve different Gram (+)ve specifi c and broad spectrum antibiotics (Table 1). Broadly, the isolates were resistant to the penicillin group but strictly, the BT1 and 2 were resistant to penicillin, ampicillin and amoxicillin; BT4 was resistant to penicillin and ampicillin and BT5 is resistant to ampicillin and amoxicillin (Table 1) which was in agreement with other Bt 4,9 . The biochemical and physiological characters revealed that the BT3, 7, 9, 11 and 12 were similar i.e.…”
Section: Introductionsupporting
confidence: 77%
“…In the present study, B. cereus was found susceptible to Aminoglycosides (gentamycin, neomycin and streptomycin) and chloramphenicol which is similar to the results of Luna et al, (2007) who reported that B. cereus isolates were susceptible to aminoglycosides, chloramphenicol, clindamycin, erythromycin, tetracyline and vancomycin. Previous works on the antimicrobial susceptibility of B. cereus revealed higher sensitivity towards ampicillin, amoxicillin and less susceptible to streptomycin, chloramphenicol, and neomycin as reported by Turnbull et al, (2004), Meena et al, (2000) and Schlegova et al, (2003). However erythromycin showed a resistance of (27.2%) which is in agreement to Wong et al, (1988) as some B. cereus isolates could attain resistance due to indescriminate use of these antibiotics in feeds and chemotherapy.…”
Section: Antibiogram Of B Cereus Isolatesmentioning
confidence: 82%
“…The current Centers for Disease Control recommendations for treatment following potential exposure to aerosolized B. anthracis spores calls for administration of antibiotics for at least 60 d and the licensed protective antigen-based vaccine (1). However, antibiotic treatment can be ineffective when bacterial strains are antibiotic resistant (2). An alternative to treatment with antibiotics is desirable.…”
mentioning
confidence: 99%